Comparison between Rose Bengal and indirect ELISA tests for detection of the antibrucella antibodies in serum of sheep in Mosul city - S. H. Arslan; Kh. J. Hussain; S. A. Asmaeel; S. D. Hassan (Iraqi Journal of Veterinary Sciences, 2010)
The aim of the present study was to determine seroprevalence of brucellosis in non vaccinated sheep in different areas inMosul city, and make a comparison between Rose Bengal and indirect ELISA tests for the diagnosis of the Brucellosis insheep. The study included examination of 228 serum samples representing 1906 sheep distributed in ten flocks.The results ofRose Bengal test showed that total seroprevalence of brucellosis was (8.7%), being highest in Talkaf (40%), while noseroprevalence of Brucellosis was recorded in Al-Rashedia, Bazwaya and Al-Chaban areas. Using indirect ELISA test the totalseroprevalence was (23.6%) and the highest percentage (100%) was in Al-Namrood area, but lowest (5.2%) in Bazwaya area.The results showed that the compatibility between the two tests was (0.380) on Kappa value which indicated that the indirectELISA test is more sensitive when compared with Rose Bengal test in detection of antibodies of Brucellosis in serum sheep.